Obstructive Fecalomas in an Infant Treated with Successful Endoscopic Disimpaction. (3rd February 2021) - Kanai, Risa; Nakaya, Kengo; Fukumoto, Koji; Yamoto, Masaya; Miyake, Hiromu; Nomura, Akiyoshi; Yamada, Susumu; Makino, Akihiro; Iwafuchi, Hideto; Urushihara, Naoto
Abstract : A fecaloma is a mass of accumulated feces with a consistency much harder than that of a fecal impaction. It is most frequently observed in the rectum and sigmoid area, and associated complications include colonic obstruction, ulceration, bleeding, and perforation. A one-year-old, previously healthy boy with no history of chronic constipation was admitted because of vomiting and abdominal distension. An abdominal computed tomography scan showed small and large bowel distension due to multiple obstructive fecalomas in the transverse colon. As the fecalomas could not be resolved by laxatives, enemas, or colonic lavage, endoscopic disimpaction under general anesthesia was attempted. Repeatedly shaving the fecalomas with biopsy forceps finally resulted in gradual fragmentation with subsequent passage. Gastrointestinal food allergy was later suggested as the cause because eosinophilic infiltration was found in a biopsy specimen of the colon wall. Endoscopic disimpaction is an effective treatment approach for addressing fecalomas to avoid more invasive surgical intervention.